MiR-27 and MiR-145 mediate neural differentiation signaling pathways in dental pulp stem cells - Hunter Triplett; Charlton Bassett; Karl Kingsley; Katherine M. Howard (Academia Molecular Biology and Genomics, 2024)
Many types of stem cells, including mesenchymal stem cells or MSCs, may be useful in the tissue regeneration of many cell and tissue types. Recent studies have found that dental pulp stem cells (DPSCs) may also be capable of differentiating into bone, tooth, and possibly neural progenitors. To evaluate the potential mechanisms that control this differentiation among DPSCs, previous work identified two potential microRNA targets, miR-27 and miR-145, using an existing DPSC biorepository and n = 12 DPSC lines treated with neural differentiation stimuli (epidermal growth factor or EGF, and basic fibroblast growth factor or bFGF), as well as non-treated (negative) controls. The goal of this project was to evaluate whether downstream targets of microRNAs miR-27 and miR-145 found in MSC neural differentiation are also involved in the regulation of neural differentiation in DPSCs. Using the RNA derived from previous studies, this retrospective analysis screened validated downstream targets and revealed differences between significant mRNA expressions of control and treated DPSCs, including miR-27-specific targets INO80D, BTF3, HECW2, and ADCY1, as well as miR-145 downstream targets FSCN1 and SRGAP2, which may be neural differentiation mediators in other types of MSCs. These results suggest that these targets may play significant roles in the neuronal differentiation pathway of DPSCs, which supports the theory that DPSCs and the microRNAs that control their development may be critical in the development of treatments for neurodegenerative diseases. Further research is needed to continue exploring the viability of these pathways as targets for treatment development.